HPV VACCINATION IN LOW-RESOURCE SETTINGS : OVERCOMING BARRIERS TO IMPLEMENTATION - Virmani, S.; Sattarova, K.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Background: Human Papillomavirus (HPV) vaccination is a cornerstone in cervical cancer prevention. Despite available vaccines, coverage remains low in low-resource settings due to cost, vaccine hesitancy, and infrastructure challenges[1][2]. Materials and Methods: This narrative review analyzed data from six low-resource countries (India, Uzbekistan, Ukraine, Russia, Pakistan, and Sri Lanka) using published literature and official health reports (2000–2024). Comparative assessment was performed with high-income and upper-middle-income countries. Results: Major barriers included affordability ( 75/dose)[3], cultural resistance, and poor rural outreach [1]. In contrast, countries like Australia, the UK [4], Rwanda, and Bhutan reported >70–90% coverage [2]. A school-based initiative in Uzbekistan showed high coverage and no adverse reactions, proving feasibility in low-resource settings. Clinical data confirm >50% reduction in HPV-related cancer rates post-vaccination [5][6]. Conclusion: Addressing HPV vaccination gaps in LMICs requires subsidized vaccine delivery, awareness programs, and international collaborations. School-based delivery offers a scalable solution for improving coverage.